2008
DOI: 10.1093/ndt/gfn703
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor expression is increased via 12-lipoxygenase in high glucose-stimulated glomerular cells and type 2 diabetic glomeruli

Abstract: These results indicate that AT1 expression is enhanced, at least in part, by 12-LO in the type 2 diabetic glomeruli, and 12-LO inhibition can ameliorate DN progression through downregulation of AT1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 36 publications
3
46
0
Order By: Relevance
“…14 The molecular pathways contributing to podocyte injury in DN include, but are not limited to, high glucose and activation of the local renin-angiotensin system (RAS). 15 Angiotensin (Ang) II is one of the major effector molecules of the RAS and is the main target of established therapy for clinical DN. 15 Intraglomerular Ang II levels are increased in DN, 16 podocytes express Ang II receptors 17 and local glomerular RAS directly promotes filtration barrier injury.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…14 The molecular pathways contributing to podocyte injury in DN include, but are not limited to, high glucose and activation of the local renin-angiotensin system (RAS). 15 Angiotensin (Ang) II is one of the major effector molecules of the RAS and is the main target of established therapy for clinical DN. 15 Intraglomerular Ang II levels are increased in DN, 16 podocytes express Ang II receptors 17 and local glomerular RAS directly promotes filtration barrier injury.…”
mentioning
confidence: 99%
“…15 Angiotensin (Ang) II is one of the major effector molecules of the RAS and is the main target of established therapy for clinical DN. 15 Intraglomerular Ang II levels are increased in DN, 16 podocytes express Ang II receptors 17 and local glomerular RAS directly promotes filtration barrier injury. 15 Ang II promoted apoptosis of the cultured rat and mouse podocytes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One of the renal hemodynamic effects of Ang II was assumed to be the increase in the products of the 12-lipoxygenase (12-LO) pathway (2). To support this early study (2), we demonstrated recently that the upregulation of AT1 is associated with the activated 12-LO pathway in the diabetic kidneys and the mesangial cells exposed to high levels of glucose (27,29).The 12-LO pathway derives several products to exert numerous physiological and pathological effects in the kidney. …”
mentioning
confidence: 80%
“…Both 12-LO and 12(S)-HETE were implicated in DN (10,22,27,29). However, how 12-LO induces renal dysfunction remains under investigation.…”
Section: One Of the 12-lo Products Is The Formation Of Oxidized Lipidmentioning
confidence: 99%